Segment Length in Cine Strain Analysis Predicts Cardiac Resynchronization Therapy Outcome Beyond Current Guidelines. (July 2021) - Zweerink, Alwin; Friedman, Daniel J.; Klem, Igor; van de Ven, Peter M.; Vink, Caitlin; Biesbroek, P. Stefan; Hansen, Steen M.; Kim, Raymond J.; van Rossum, Albert C.; Atwater, Brett D.; Allaart, Cornelis P.; Nijveldt, Robin
Abstract : Background: Patients with a class I recommendation for cardiac resynchronization therapy (CRT) are likely to benefit, but the effect of CRT in class II patients is more heterogeneous and additional selection parameters are needed in this group. The recently validated segment length in cine strain analysis of the septum (SLICE-ESSsep ) measurement on cardiac magnetic resonance cine imaging predicts left ventricular functional recovery after CRT but its prognostic value is unknown. This study sought to evaluate the prognostic value of SLICE-ESSsep for clinical outcome after CRT. Methods: Two hundred eighteen patients with a left bundle branch block or intraventricular conduction delay and a class I or class II indication for CRT who underwent preimplantation cardiovascular magnetic resonance examination were enrolled. SLICE-ESSsep was manually measured on standard cardiovascular magnetic resonance cine imaging. The primary combined end point was all-cause mortality, left ventricular assist device, or heart transplantation. Secondary end points were (1) appropriate implantable cardioverter defibrillator therapy and (2) heart failure hospitalization. Results: Two-thirds (65%) of patients had a positive SLICE-ESSsep ≥0.9% (ie, systolic septal stretching). During a median follow-up of 3.8 years, 66 (30%) patients reached the primary end point. Patients with positive SLICE-ESSsep were at lower risk to reach the primary end point (hazard ratio 0.36; P <0.001) and heart failure hospitalization (hazard ratio 0.41; P =0.019), but not for implantable cardioverter defibrillator therapy (hazard ratio, 0.66; P =0.272). Clinical outcome of class II patients with a positive ESSsep was similar to those of class I patients (hazard ratio, 1.38 [95% CI, 0.66–2.88]; P =0.396). Conclusions: Strain assessment of the septum (SLICE-ESSsep ) provides a prognostic measure for clinical outcome after CRT. Detection of a positive SLICE-ESSsep in patients with a class II indication predicts improved CRT outcome similar to those with a class I indication whereas SLICE-ESSsep negative patients have poor prognosis after CRT implantation.